PEMBERDAYAAN EKONOMI KREATIF MELALUI PENGEMBANGAN SENTRA KERAJINAN BAMBU BERBASIS KEARIFAN LOKAL DI DESA SUKASARI KECAMATAN TUNJUNGTEJA - Hendrawati, Sulkiah; Meiby Zulfikar; Ulfi Jefri; Ira Damayanti; Agustina Dwiyanti; Nia Marlina Kurnia; Mokhamad Mahroji; Andini Nur fatimah; Arif Hidayat; Adi Setiadi (Jurnal Akselerasi Merdeka Belajar dalam Pengabdian Orientasi Masyarakat (AMPOEN): Jurnal Pengabdian kepada Masyarakat, 2025)
This community service activity aims to increase the capacity and competitiveness of business actors in bamboo craft centers through a creative economic empowerment approach based on local wisdom. Bamboo craft centers have great potential as a source of livelihood for the community and as a cultural preserver, but face obstacles such as limited design innovation, limited market access, and less than optimal use of technology. The implementation method includes product design training based on market trends, technical production assistance, strengthening branding strategies, and utilizing digital media for marketing. The results of the activity showed an increase in craftsmen’s skills in creating innovative products that maintain local cultural values, with 85% of participants being able to produce at least three new designs ready for marketing. In addition, there was an increase in product quality, resulting in an average increase in sales of 37% in the three months following the assistance, as well as the opening of online market access that successfully reached consumers in five different provinces. This empowerment is expected to not only increase community income but also strengthen cultural identity through the sustainable management of bamboo craft centers.